How can Clinicians Do A Good Job in RCT Research - SHEN Kaini; LI Jian (Xiehe Yixue Zazhi, 2023)
Randomized controlled trial(RCT) provides the most valid means of establishing the efficacy of clinical therapeutics. A good RCT should be based on topics with clinical significance and scientific value, and focus on the establishment of intervention and control, the method of randomization and the selection of primary endpoints. During the implementation process, details such as ethics application, research registration, data collection and regular review of the research are of great value to ensure the scientific validity of the trials and the credibility of the results.